KANCHNARA (BAUHINIA VARIEGATA LINN.): A CRITICAL REVIEW - Ramesh Chandra, Tewari; Suresh, Chaubey; Sanghamitra, Dash; Gagan deep, Kour; Rajnish Kumar, Gautam (International Journal of Ayurveda and Pharma Research, 2015)
Kanchnara also called Mountain Ebony in English has been used in Ayurvedic system of Medicine since a long period. Different species of Bauhinia are known and used as Kanchnara in Ayurvedic medicine. It is a moderate sized deciduous tree with greyish colored stem found in Sub Himalayan tract from the Indus eastwards and throughout the forests of India and Burma. Maharishi Charaka and Sushruta have mentioned the properties of Kovidara and Karbudara in their Samhitas (Treatise). Both flower and bark of Kanchnara are used as medicine because of the important chemical constituents present in them which are hentriacontane, octacosanol, b-sitasterol, stigmasterol, lupeol and amino acids. The drug has been described as Grahi, Krimighna, Kushtaghna, Gandamalanashaka, Vranaropaka, Mehaghna and Raktapittashamak. Considerable efforts have been made by researchers to study the chemical and biological potential of the plant. The reported pharmacological activities of Bauhinia variegata Linn. are anti-diabetic, anti-ulcer, anti-oxidant, nephroprotective, anti-cancer, hepatoprotective, anti-inflammatory, immunomodulatory, anti-microbial, anti-bacterial. Kanchanara is one of the major ingredient of many important formulations used in Ayurveda system of medicine such as Kanchanara Guggulu, Kanchan gutika, Gandamala kundan rasa, Gulkand Kanchanara and Kanchanaradi Kwatha,Ushirasava, Chandanasava, Vidangarishta, Kanchanara drava, Kanchnara Varuna Kwatha. So this review paper is an endeavour of the author to provide details of this medicinal plant Kanchnara about its classical references, synonyms, botanical description, phytochemicals, pharmacological activity and classical medicinal uses.